Optimalisasi Manajemen SDM Melalui Pengembangan Aplikasi Mobile Absensi dan Perizinan Digital pada Lembaga Amil Zakat Yatim Mandiri - Rohman, Trian Basofi; Shobikhah, Anis; Kurnoasari, Norma Devi; Triono, Gaguk; Widianto, Ari (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2025)
In the current digital era, manual attendance systems are increasingly being abandoned due to inefficiencies, susceptibility to data manipulation, and time-consuming recap processes—particularly in large-scale organizations with over 500 employees spread across multiple provinces and two different time zones. The main challenges of manual systems include delayed data validation, inconsistency in attendance timing across regions, and difficulties in generating real-time integrated reports. To address these issues, this study developed a location-based (GPS), mobile, and real-time attendance application using the Rapid Application Development (RAD) approach, which emphasizes fast prototyping and active user involvement. The application was built using React Native for cross-platform mobile interfaces (iOS and Android), PHP Laravel for the backend, and PostgreSQL along with Firebase Cloud Messaging for database and notification services. Testing results show that the application achieves a location accuracy rate of 95%, reduces approval processing time from over one day (manual) to an average of 1–2 minutes, and ensures 100% success in real-time notification delivery. Additionally, the application simplifies cross-time-zone attendance recapitulation and achieved a user satisfaction rate of 92% based on a User Acceptance Test (UAT) involving 50 respondents from various branches. These findings indicate that the developed application is effective in enhancing operational efficiency, data accuracy, and transparency in the digital and integrated management of employee attendance.